Review on phase change material emulsions for advanced thermal management: Design, characterization and thermal performance. (May 2022) - Cabaleiro, D.; Agresti, F.; Fedele, L.; Barison, S.; Hermida-Merino, C.; Losada-Barreiro, S.; Bobbo, S.; Piñeiro, M.M.
Abstract: Interest in phase change material emulsions (PCMEs) as advanced thermal storage and heat transfer media is growing and this is leading to an increase in the number of articles on the subject. This review attempts to summarize previous research on formulation, thermophysical, rheological, hydrodynamics and heat transfer properties of PCMEs in order to provide an insight of the advantages and challenges of these novel materials. Specific attention is paid to experimental investigations on emulsion stability during storage time, but also under freeze-thaw cycling, shear mechanical stresses or other operational conditions in which materials must work in thermal facilities. Main outcome of phase change characteristics is discussed, analyzing strategies proposed in the literature to address undesirable sub-cooling phenomena. The influence of droplet size, surfactant type or dispersed phase concentration on other thermophysical and rheological properties is also revised in order to further understand how those parameters affect storage capacity and thermo-hydrodynamic performance of PCMEs. Finally, the article provides an overview of the potential of phase change material emulsions for efficient thermal management and promoting the use of renewables in different industrial fields. Graphical abstract: Image 1 Highlights: Progresses on phase change material emulsions as heat transfer media are reviewed. Thermal, rheological, hydrodynamics and heat transfer properties are summarized. Emulsion stability in operating conditions is widely investigated. Challenges for their use in thermal management systems and renewables are outlooked.